2011
DOI: 10.1111/j.1747-0803.2011.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Women with Congenital Heart Disease: The Impact of a Systemic Right Ventricle

Abstract: In women with congenital heart disease, a systemic right ventricle is associated with adverse cardiac and pregnancy outcomes. This information is critical for counseling and caring for these women. Further investigation is warranted regarding the effect of pregnancy on long-term health for this unique cohort of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…4,5,911 In a study of 562 pregnant women with heart disease receiving care in 13 Canadian cardiac and obstetric teaching hospitals, Siu et al 10 found that composite cardiovascular outcome (pulmonary edema, arrhythmia, stroke, or cardiac death) complicated 13% of 617 pregnancies. Two other groups of researchers have utilized the Nationwide Inpatient Sample to determine associated outcomes among pregnant women with CHD; both studies primarily focused on cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,911 In a study of 562 pregnant women with heart disease receiving care in 13 Canadian cardiac and obstetric teaching hospitals, Siu et al 10 found that composite cardiovascular outcome (pulmonary edema, arrhythmia, stroke, or cardiac death) complicated 13% of 617 pregnancies. Two other groups of researchers have utilized the Nationwide Inpatient Sample to determine associated outcomes among pregnant women with CHD; both studies primarily focused on cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated a composite cardiovascular outcome because it was used in previous studies that included any one of the following: in-hospital mortality, myocardial infarction, cardiac arrest, arrhythmia, heart failure, or stroke. 10,11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, codes for DiGeorge syndrome, Wiskott Aldrich syndrome, and X-linked agammaglobulinemia were more stable; the data attached to these cases is likely to be more reliable. The use of codes has been established in other recent studies: the assessment of rotavirus vaccination acute gastroenteritis [42], methicillin-resistant Staphylococcus aureus infections [43], outcomes of pregnancy in patients with congenital heart disease [44], risk of melanoma in rheumatoid arthritis [45], and drug induced acute liver toxicity [46]. In clinical immunology, ICD codes have been used to demonstrate that the use of intravenous immune globulin was associated with reduced risk of Alzheimer’s disease [47].…”
Section: Discussionmentioning
confidence: 99%
“…29 Supraventricular arrhythmias appear to be common, but significant decline in systemic ventricular function does not appear to occur in the short term related to pregnancy. 30 Successful pregnancy can be achieved in most women with TGA; however, the rate of fetal loss and maternal cardiovascular morbidity is increased.…”
Section: Ebstein Anomalymentioning
confidence: 96%